Urinary oxidative stress biomarker levels and reproductive outcomes among couples undergoing fertility treatments. Issue 12 (30th December 2019) - Rosen, E M; Mínguez-Alarcón, L; Meeker, J D; Williams, P L; Milne, G L; Hauser, R; Ferguson, K K; ,
Abstract: STUDY QUESTION: Are urinary levels of oxidative stress biomarkers associated with reproductive outcome success following fertility treatments? SUMMARY ANSWER: Levels of oxidative stress in the middle tertile for women are associated with the highest levels of reproductive success while no associations were noted for men. WHAT IS KNOWN ALREADY: Oxidative stress may contribute to adverse fertility outcomes in the general population, but findings from couples undergoing fertility treatments are sparse. STUDY DESIGN, SIZE, DURATION: This prospective cohort study included 481 women and 249 of their male partners undergoing fertility treatments from 2007 to 2015, from the Environment and Reproductive Health (EARTH) study in Boston, MA. PARTICIPANTS/MATERIALS, SETTING, METHODS: One urine sample per participant was collected at each cycle and analysed for two oxidative stress markers: 8-isoprostane-PGF2α (8-iso-PGF2α ) and 8-isoprostane-PGF2α metabolite (F2 -isoP-M). Reproductive outcomes were abstracted from medical records and included the fertilization rate, for IVF (oocytes fertilized/mature oocytes retrieved), and rates of implantation, clinical pregnancy and live birth, for both IVF and IUI. Cluster-weighted generalized estimating equations were used to analyse adjusted associations between exposure tertiles and outcomes. MAIN RESULTS AND THE ROLE OF CHANCE: Levels of F2 -isoP-M in the middle tertile were associated with the most success among women. Women in the upper tertile of F2 -isoP-M had an adjusted mean live birth rate after IVF and IUI of 23% (95% CI: 17, 29) compared to 38% (95% CI: 31, 45) for women in the middle tertile and 27% (95% CI: 21, 34) in the lower tertile. The fertilization rate during IVF was higher for women with 8-iso-PGF2α in the middle tertile (0.77 [95% CI: 0.73, 0.80]) compared to women in the lower (0.69 [95% CI: 0.64, 0.73]) or upper tertiles (0.66 [95% CI: 0.61, 0.71]). No significant associations were found for other measured outcomes with 8-iso-PGF2α, or between any oxidative stress biomarker in men and reproductive outcomes in their partners. LIMITATIONS, REASONS FOR CAUTION: Isoprostanes are short-lived biomarkers and this study may not have captured the most relevant window of susceptibility for oxidative stress on the outcomes of interest. Findings from this study may not be generalizable to couples attempting conception without fertility assistance. WIDER IMPLICATIONS OF THE FINDINGS: This study suggests that a non-linear association may exist between oxidative stress and reproductive outcomes in a population undergoing fertility treatment, a finding not previously identified in the literature. Oxidative stress may represent the mechanism through which environmental chemicals are associated with adverse reproductive outcomes. STUDY FUNDING/COMPETING INTEREST(S): This research was supported by the Intramural Research Program of the National Institutes of Environmental Health Sciences (NIEHS) (ZIA ES103314) and by NIEHS grants R01ES022955, R01ES009718 and R01ES00002. There are no competing interests to report. TRIAL REGISTRATION NUMBER: N/A